Assessing neuropsychiatric symptoms in people with dementia: a systematic review of measures. (November 2014) - Gitlin, Laura N.; Marx, Katherine A.; Stanley, Ian H.; Hansen, Bryan R.; Van Haitsma, Kimberly S.
ABSTRACT Background: Neuropsychiatric symptoms (NPS) occur in people with dementia throughout disease course and across etiologies. NPS are associated with significant morbidities and hastened disease processes. Nevertheless, people with dementia are not systematically assessed for NPS in clinical settings. We review existing NPS measures for clinical and/or research purposes, and identify measurement gaps. Methods: We conducted a computerized search of peer-reviewed published studies of measures (January 1, 1980–December 1, 2013) using multiple search terms. Measures selected for review were in English, had adequate psychometric properties, and were developed for or used with people with dementia. Papers describing measures were evaluated by three coders along seven characteristics: behavioral domains, number of items, method of administration, response categories, targeted population, setting, and psychometric properties. Results: Overall, 2, 233 papers were identified through search terms, and 36 papers from manual searches of references. From 2, 269 papers, 85 measures were identified of which 45 (52.9%) had adequate psychometric properties and were developed or used with dementia populations. Of these, 16 (35.6%) were general measures that included a wide range of behaviors; 29 (64.4%) targeted specific behaviors (e.g. agitation). Measures differed widely as to behaviors assessed and measurement properties. Conclusions: A robust set of diverse measures exists for assessing NPS in different settings. No measures identify risk factors for behaviors or enable an evaluation of the context in which behaviors occur. To improve clinical efforts, research is needed to evaluate concordance of behavioral ratings between formal and informal caregivers, and to develop and test measures that can identify known risks for behaviors and the circumstances under which behaviors occur.